A moisture-dependent thermomechanical constitutive model for concrete subjected to transient high temperatures. (1st May 2020) - Torelli, Giacomo; Gillie, Martin; Mandal, Parthasarathi; Draup, Jefri; Tran, Van-Xuan
Highlights: A novel moisture-dependent thermal strain model for concrete is presented. The moisture-dependent parts of concrete thermal strain are modelled explicitly. The presented model is verified and validated against published experiments. Nuclear vessels are affected by the moisture-dependency of concrete thermal strain. Abstract: This paper presents a constitutive model for concrete able to capture the effects of the moisture content of the material on its mechanical behaviour under compressive loads and high transient temperatures. The model is the first to account for the experimentally demonstrated effect of moisture content on the two components of thermal strain, Load Induced Thermal Strain (LITS) and Free Thermal Strain (FTS). Both LITS and FTS are formulated as functions of the water content of the material at the beginning of the thermal transient. First, the theoretical formulation and numerical implementation of the model are presented. Then, the model is verified and validated against published transient tests on concrete specimens having different initial moisture contents. Finally, it is employed to assess a representative nuclear pressure vessel subjected to fault conditions. The results show that the model allows the moisture dependent behaviour of concrete heated under mechanical load to be accurately captured. Furthermore, it is shown the introduction of moisture-dependent thermal strain components is crucial to capture the behaviour of nuclear pressure vessels subjected to fault conditions. If the moisture-dependency of thermal strain of concrete is not considered, non-conservative results may be obtained.